The Cigarette Smoking Initiation and Continuation in Adolescents Undergoing a Long-Term Behavioral Intervention. Issue 4 (12th October 2020) - Masihay-Akbar, Hasti; Amiri, Parisa; Cheraghi, Leila; Momenan, Amir Abbas; Azizi, Fereidoun
Abstract: Introduction: Targeting adolescents' smoking reduces its burden on health systems. We investigated the effects of the first multidisciplinary community-based lifestyle intervention in the Eastern Mediterranean region, on smoking initiation, continuation, and risk of current smoking in Iranian adolescents. Methods: The current analyses were conducted on 945 nonsmoker adolescents (12–18 years) who participated in Phase II of Tehran Lipid and Glucose Study (TLGS) and were examined four times in 12 years. The lifestyle intervention including school-based and public programs was implemented, focusing on all components of healthy lifestyle. Using a two-step cluster analysis, families were classified as high and low risk, based on parental risk factors of adolescents' smoking. Participants who failed to complete all the follow-ups ( n = 99) and those with missing smoking data were excluded. Subsequently, 872 adolescents (538 control, 334 intervention) were included in the Cox model on smoking initiation, and 674 adolescents (414 control, 260 intervention) were included in the logistic regression on smoking status. Results: Mean age of adolescents was 15.08 ± 1.94 years at baseline. The hazard of the smoking initiation was significantly lower in the intervention (hazard ratio = 0.71, 95% confidence interval: 0.51–0.99; p = .044) compared with control group. At the end of the fourth follow-up, intervention reduced the odds of current cigarette smoking by 29%. Within the intervention group, the high-risk cluster was at a 35% lower risk of initiating smoking and had 37% lower odds of becoming a current smoker. However, the intervention could not make a difference in preventing those who initiated smoking from maintaining it during the follow-ups. Conclusions: Our results demonstrate that lifestyle modification programs targeting at-risk populations could reduce risk of smoking initiation and current smoking in adolescents in long term. Implications: Experiencing cigarette smoking at the critical period of adolescence could result in adulthood habitual smoking. Therefore, identifying adolescents who are more at risk of smoking initiation and implementing targeted interventions are of great importance in public health. Our findings highlight the long-term effectiveness of a multidisciplinary community-based behavioral intervention on forming smoking behaviors in adolescents. The current intervention was successful in reducing smoking uptake in adolescents living in high-risk families.